Mechanistic General Education and Komsomol Using the Example of the Social Movement for the Creation of the “Komsomolets of Kalmykia” tractor column - Baatr A. Okonov (Монголоведение)
Introduction. The article attempts to highlight the process of mass training in machine-building specialties of the rural population in the Kalmyk ASSR, which, due to the lack of agricultural machinery, resulted in a public movement for the creation of a tractor column "Komsomolets of Kalmykia". The purpose of the study, based on published and unpublished sources, is to highlight the role of the Komsomol in conducting mass training in machine-building specialties in the Kalmyk ASSR. Materials and methods The source base was the materials of the National Archive of the Republic of Kalmykia. The analysis of archival materials was carried out using such methods as periodization, which provided an opportunity to trace qualitative changes in the process of forming a social movement and an analysis of the main trends and contributions of participants in the movement for the creation of the Komsomolets Kalmykia tractor column. Results and conclusions. The article shows the situation in agriculture on the eve of the mechanized general education in the Kalmyk ASSR. Special attention is paid to the contribution of both direct participants in the movement and collective farms, state farms and districts to the fund of the Komsomolets Kalmykia tractor column. The author concludes that a significant increase in the number of agricultural machinery and the introduction of new models required comprehensive training in rural areas. During the period of the mechanization general education in Kalmykia, thousands of boys and girls in villages received mechanization specialties. Due to the shortage of new samples of agricultural machinery, Komsomol members proposed to create a fund for the Komsomolets Kalmykia tractor column. The result of the movement for the creation of a tractor column was the provision of the necessary machine and tractor fleet for educational enterprises. At the same time, throughout the 1970s, the problem of leakage of mechanized personnel persisted.